1997
DOI: 10.1111/j.1540-8167.1997.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐Sensitive Bundle Branch Reentry

Abstract: Patients with ventricular tachycardia involving a bundle branch reentrant circuit may be sensitive to adenosine. These results suggest that adenosine may not only inhibit catecholamine-mediated triggered activity but also some catecholamine-mediated reentrant ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The effect of adenosine on these tachycardias has not been systematically studied, although adenosine is generally not believed to influence conduction in the His–Purkinje system. Nonetheless, there is at least 1 report of BBR VT induced during isoproterenol infusion that reproducibly terminated with adenosine 4 . Finally, the echocardiographic findings are compatible with all 3 tachycardias.…”
Section: Commentarymentioning
confidence: 70%
See 1 more Smart Citation
“…The effect of adenosine on these tachycardias has not been systematically studied, although adenosine is generally not believed to influence conduction in the His–Purkinje system. Nonetheless, there is at least 1 report of BBR VT induced during isoproterenol infusion that reproducibly terminated with adenosine 4 . Finally, the echocardiographic findings are compatible with all 3 tachycardias.…”
Section: Commentarymentioning
confidence: 70%
“…Nonetheless, there is at least 1 report of BBR VT induced during isoproterenol infusion that reproducibly terminated with adenosine. 4 Finally, the echocardiographic findings are compatible with all 3 tachycardias. While often associated with dilated cardiomyopathy, BBR VT has occasionally been reported in the setting of isolated conduction system disease with no apparent structural heart abnormalities.…”
Section: Commentarymentioning
confidence: 77%
“…In another case study, BBRT with no structural heart disease was reproducibly terminated by intravenous adenosine (35). During an electrophysiology study, BBRT was repeatedly initiated by isoproterenol infusion, suggesting that it originated from triggered activity (35). Schafferhofer-Steltzer et al (37) have also shown how to induce EADs in Purkinje fibers by locally superfusing them with isoproterenol solution.…”
Section: Arrhythmia Induction By Triggered Activitymentioning
confidence: 96%
“…Nicorandil was found to abolish VT arising from afterpolarizations in long-QT syndrome. In another case study, BBRT with no structural heart disease was reproducibly terminated by intravenous adenosine (35). During an electrophysiology study, BBRT was repeatedly initiated by isoproterenol infusion, suggesting that it originated from triggered activity (35).…”
Section: Arrhythmia Induction By Triggered Activitymentioning
confidence: 98%
“…BBRVT is the only one of these clinical entities that usually exhibits no response to adenosine [36] . Although administration of adenosine may occasionally result in VA dissociation during hemodynamically stable VT, it should be noted that BBRVT is usually rapid and hemodynamically unstable, making DC cardioversion the initial option of choice.…”
Section: Diagnostic and Acute Therapeutic Maneuversmentioning
confidence: 99%